Being Entrepreneurial in the Transitional Indonesian Economy - Lock, Rob (Auckland University of Technology, 2015)
This thesis makes a contribution to a comprehensive theory on entrepreneuring. It develops and illustrates the concept of ‘being entrepreneurial’ with reference to innovative ventures in politics, business and the military in Indonesia from 1908 to 1998. The study applies two Foucauldian-inspired methods. The method of analysis developed by Michel Foucault in The birth of bio politics, with additional influences of Gilles Deleuze and Pierre Bourdieu, is used to expand the theoretical scope of entrepreneurial activities. In analysing events from Indonesian history to illustrate the expanded theoretical scope, a Foucauldian-influenced discourse analysis is used, including a focus on aspects of power and heterotopias. The concept of ‘being entrepreneurial’ focuses on viewing the processes in innovative ventures to determine post factum which of these processes could be determined to be more, or less, entrepreneurial, rather than, as is more traditionally the case, a priori attributes being assigned to ‘an entrepreneur’ whose traits and/or processes employed are then studied. In this thesis, a deliberate effort has been made to expand the scope of entrepreneurial activities beyond their conventional association with commercial new ventures, historical capitalism and an inherent goodness. This expanded scope enables a more inclusive view of entrepreneurial activity than has often been the case. With this expanded scope, a range of innovative ventures within the chosen Indonesian historical context were examined to determine whether these innovative ventures could be considered more or less entrepreneurial, rather than decisions made on the basis of any a priori attribution to ‘an entrepreneur’. These innovative ventures were located through careful reading of some 1200 articles, books, theses, reports and news articles on Indonesian history, including both general historical references and those with a more specific focus on political and business aspects as well as entrepreneurship articles in general. These texts became the basis of the discourse analysed. From the analysis it became apparent that there were not only particular exclusions, such as silences relating to corruption, but also the views of certain authors had heavily influenced some parts of the discourse. To allay some of the effects of these exclusions and influences, local input within Indonesia was sought. Conversations were held with 20 individuals in Indonesia who were considered to have experience and expertise in history, politics, business, media and academia. These conversations were useful in providing confirmation or disconfirmation of the interpretations arising from the discourse analysis. The main findings from the research were that while particular individuals, such as Soetadjo, Tjokroaminato, Nitisemito, Hatta, Soekarno, Suharto and Ibnu Sutowo ‘stood-out’ in their innovative ventures, an analysis of the manner in which they achieved such status indicated that their standout properties were not so much due to individualism, but more to the manner in which they ‘selected the relevancies’ of who and what to work with, and in particular the way they exercised power by ways of alignments and local arrangements. This latter point is highlighted with the Cultivation System which encouraged ‘entrepreneur-less’ innovations. The manner, in which the changing of alignments enabled the innovative process to be sustained for extended periods, is illustrated with reference to Suharto’s 32 year rule. Further findings suggested a propensity to enclave as being beneficial to supporting innovative ventures. This propensity to enclave is illustrated by reference to the hamlet of Laweyan where a distinct commercially-orientated culture developed, at odds with the prevailing local Javanese culture. A similar illustration is given with the political enclave that developed around Tjokroaminato in Surabaya that produced many of the leading political figures of the late colonial period. This propensity to enclave is interpreted as an illustration of Foucault’s heterotopia of deviation. Foucault’s other heterotopia - that of crisis heterotopia (diaspora) - is illustrated by the Minangkabau people of Western Sumatra who manifested stand-out properties in business, politics and academia. The institutional setting of the Minangkabau people, including a culturally enforced diaspora, illustrates how these stand-out properties could have originated. The main contribution of this thesis towards a comprehensive theory is the development of a template. This template is an ontological construction that stresses the need to focus on innovative ventures within the expanded scope mentioned above, and determine whether such ventures are more, or less, entrepreneurial. There is need to look at not only what was produced by the innovative venture, but also how it was produced, and the contextual aspect of institutional setting in which it developed. In this thesis the template is applied within a two part frame of reference. First it is argued that the quantum and acceleration of accumulation of capital could be used as a basis on which to determine whether what was produced by the innovative venture is more, or less, entrepreneurial. Second the uniqueness or stand-out qualities by which resistance was overcome through the selection of relevancies and the management of alignments could be used to determine whether the how by which the innovative venture accumulated ‘capital’ is more, or less, entrepreneurial. This thesis thus offers a somewhat radical approach to the study of entrepreneurship. It builds on recent trends focusing on the processual aspects of entrepreneurial activities but suggests that the selection of such activities for future studies be based on innovative ventures that ‘stand-out’ because of what is produced by such activities, as well as particular aspects of how it was produced.
Keywords: Being entrepreneurial; Entrepreneuring; Indonesia; Transitional economies; Heterotopia; Innovative ventures; Entrepreneurship; Enclaves; Diaspora; Suharto; Soekarno; Ontic knowledge; Ontological construction